2013
DOI: 10.1039/c3cp52001c
|View full text |Cite
|
Sign up to set email alerts
|

Environment-driven reactivity of H2 on PdRu surface alloys

Abstract: The dissociative adsorption of molecular hydrogen on Pd(x)Ru(1-x)/Ru(0001) (0 ≤ x ≤ 1) has been investigated by means of He atom scattering, Density Functional Theory and quasi-classical trajectory calculations. Regardless of their surroundings, Pd atoms in the alloy are always less reactive than Ru ones. However, the reactivity of Ru atoms is enhanced by the presence of nearest neighbor Pd atoms. This environment-dependent reactivity of the Ru atoms in the alloy provides a sound explanation for the striking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
5
20
0
Order By: Relevance
“…To compare with experiments, vibrational state distributions have been computed by thermal averaging normal collision energy resolved results in the limit of normal and total energy scaling. 90 Both limits give almost identical results as vibrational state distributions depend weakly on collision energy, in particular for E proj > 0.1 eV leading to non-negligible cross-sections. Hereafter, we only consider the normal energy scaling limit.…”
Section: B Results and Discussionsupporting
confidence: 51%
“…To compare with experiments, vibrational state distributions have been computed by thermal averaging normal collision energy resolved results in the limit of normal and total energy scaling. 90 Both limits give almost identical results as vibrational state distributions depend weakly on collision energy, in particular for E proj > 0.1 eV leading to non-negligible cross-sections. Hereafter, we only consider the normal energy scaling limit.…”
Section: B Results and Discussionsupporting
confidence: 51%
“…Such ‘floating back properties’ indicated that surface alloys represented stable surface configurations. [61] Ramos et al [62] investigated the dissociative adsorption of molecular hydrogen on Pd x Ru 1-x /Ru (0001) (0 < x < 1) by means of He atom scattering, DFT and quasi-classical trajectory calculations 62 and found that in a Pd-rich surface alloy the reactivity of Ru atoms in dissociative adsorption of molecular hydrogen was enhanced by the presence of nearest neighbor Pd atoms. However, Pd atoms in the Pd-rich surface alloy were less reactive than the Ru ones regardless of their surroundings because of both electronic and strain effects.…”
Section: Near-surface Alloysmentioning
confidence: 99%
“…A clever way to do so is the pseudomorphic growth of ultrathin metallic films on top of substrates with different lattice constants. The electronic properties of the stretched (compressed) surface can be substantially modified giving rise to profound changes in the adsorption energetics between strained and unstrained surfaces [13][14][15][16][17][18][19][20]. Hitherto, all the studied systems show that the overall adsorption properties are equally altered, i.e., that the atomic, molecular, and dissociative adsorption are either all improved or all reduced.…”
mentioning
confidence: 91%